Digital Distractions and Childhood Attention: Challenges and Interventions - George, Rinu Johnsburg; Larson, Manoj; Sam, Shiny Tholidumpara (Knowledge Dynamics, 2025)
Attention span is a critical determinant of academic performance and cognitive development in children. To synthesize the literature on factors influencing attention span among school-aged children, assessment strategies, and interventions. A narrative review was conducted using articles from PubMed, Scopus, and Google Scholar between 2015 and 2024. Studies were selected based on relevance, methodological quality, and thematic alignment. Factors affecting attention span include age, sleep, screen time, nutrition, classroom environment, and neurodevelopmental conditions. Interventions such as mindfulness, physical activity, and structured classroom routines showed positive effects. Attention span is influenced by multifaceted factors. Holistic, evidence-based approaches are required to enhance attention in school children.